Combatting ischemia reperfusion injury from resuscitative endovascular balloon occlusion of the aorta using adenosine, lidocaine and magnesium: A pilot study. Issue 6 (December 2021) - Conner, Jeff; Lammers, Daniel; Holtestaul, Torbjorg; Jones, Ian; Kuckelman, John; Letson, Hayley; Dobson, Geoffrey; Eckert, Matthew; Bingham, Jason
Abstract : BACKGROUND: Resuscitative endovascular balloon occlusion of the aorta (REBOA), a minimally invasive alternative to resuscitative thoracotomy, has been associated with significant ischemia reperfusion injury (IRI). Resuscitation strategies using adenosine, lidocaine, and magnesium (ALM) have been shown to mitigate similar inflammatory responses in hemorrhagic and septic shock models. This study examined the effects of ALM on REBOA-associated IRI using a porcine model. METHODS: Animals underwent a 20% controlled hemorrhage followed by 30 minutes of supraceliac balloon occlusion. They were assigned to one of four groups: control (n = 5), 4-hour ALM infusion starting at occlusion, 2-hour (n = 5) and 4-hour (n = 5) interventional ALM infusions starting at reperfusion. Adenosine, lidocaine, and magnesium cohorts received a posthemorrhage ALM bolus followed by their respective ALM infusion. Primary outcomes for the study assessed physiologic and hemodynamic parameters. RESULTS: Adenosine, lidocaine, and magnesium infusion after reperfusion cohorts demonstrated a significant improvement in lactate, base deficit, and pH in the first hour following systemic reperfusion. At study endpoint, continuous ALM infusion initiated after reperfusion over 4 hours resulted in an overall improved lactate clearance when compared with the 2-hour and control cohorts. No differences in hemodynamic parameters were noted between ALM cohorts and controls. CONCLUSION: Adenosine, lidocaine, and magnesium may prove beneficial in mitigating the inflammatory response seen from REBOA-associated IRI as evidenced by physiologic improvements early during resuscitation. Despite this, further refinement should be sought to optimize treatment strategies.